Precarious ethics: Toxicology research among self-poisoning hospital admissions in Sri Lanka - Sariola, S; Simpson, B (2013)
Self-harm using poison is a serious public health problem across Asia. As part of a broader effort to tackle this problem, medical research involving randomised clinical trials are used to identify effective antidotes among patients who have ingested poison. On the basis of ethnographic material collected in rural hospitals in Sri Lanka between 2008 and 2009, this article describes the conduct of trials in this unusual and difficult context. It outlines three subject positions crucial to understanding the complexity of such trials. At one level, self-poisoning admissions might be thought of as abjects, that is, stigmatised by actions that have placed them at the very limits of physical and social life. They have seriously harmed themselves in an act that often leads to death, marking the act as a suicide. Yet, this is the point when they are recruited into trials and become objects of research and experimentation. Participation in experimental research accords them particular rights mandated in international ethical guidelines for human subject research. Here the inexorable logic of trials and morality of care meet in circumstances of dire emergency. © 2013 The London School of Economics and Political Science.